Facile synthesis of Pd@Ru nanoplates with controlled thickness as efficient catalysts for hydrogen evolution reaction. Issue 30 (12th June 2018) - Han, Yu; Yan, Yucong; Wu, Zhemin; Jiang, Yi; Li, Xiao; Xu, Qingfeng; Yang, Xiaofang; Zhang, Hui; Yang, Deren
Abstract : Pd@Ru nanoplates with controlled thickness were synthesized and exhibited substantially enhanced properties for the hydrogen evolution reaction relative to commercial catalysts. Abstract : Ru-based nanoplates have received considerable attention in recent years because of their attractive catalytic properties originating from their unique two-dimensional structure. However, the synthesis of Ru-based nanoplates, especially for the thickness control at the atomic level, still remains challenging. Here we report the synthesis of Pd@Ru core–shell nanoplates, in which Ru atoms exhibit a face-centered cubic ( fcc ) structure rather than a hexagonal close-packed ( hcp ) structure of bulk Ru. The thickness of Pd@Ru nanoplates and even the crystal structure of Ru shells can be tuned by simply varying the amount of the Ru precursor. The Pd@Ru nanoplates first exhibit a remarkable increase in specific activity for the hydrogen evolution reaction (HER) with Ru shell thickness and then have a dramatic decrease when the thickness of the nanoplates reaches 2.6 nm due to the structure transition of Ru from fcc to hcp . Among them, the Pd@Ru nanoplates with a thickness of 2.3 nm exhibit the optimal HER activity with good stability, even outperforming commercial Ru/C and state-of-the-art Pt/C catalysts in alkaline solution.